Environmental Problems in Geography for The Eleventh Grade from The Point of View of Teachers - Nazanin Muhammad Hasan; Serwan Arab Sadq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The aim of this study is to find out the environmental problems in geography in the eleventh grade of secondary school from the point of view of teachers in the central education in Erbil, for example, based on the differences between gender and years of service, the researcher used the descriptive-analytical method, The study population consists of geography teachers in the preparatory stages, whose number reached (247) male and female teachers, The study sample consisted of (70) male and female teachers of both sexes. The research tool is a questionnaire form specific to environmental problems created by the researcher, consisting of (73) paragraphs, distributed among Five areas, namely (aerial, aquatic, rocky, biological, and population). After analyzing the data, the results showed that the level of knowledge of environmental problems from the teachers’ point of view, the geography subject, reached an arithmetic average of (4.49), which is a good percentage. There are no statistically significant differences on a variable basis. Gender and years of service, then some suggestions and recommendations represented.